Clinical features of tuberous sclerosis cases - Söğüt, Ayhan; Özmen, Meral; Sencer, Serra; Çalışkan, Mine; Aydınlı, Nur; Ertuğrul, Türkan; Peksayar, Gönül (The Turkish Journal of Pediatrics, 2002)
Tuberous sclerosis (TS) is an autosomal dominant, multisystemic and neurocutaneous disease with high spontaneous mutation rate, and it mostly involves the skin, brain, kidneys, heart and the eyes. This study included 35 patients diagnosed with tuberous sclerosis and aged 6 months to 17 years, with a mean age of 6.5 ± 4.8 years. The most frequently observed manifestations were those of the skin (97.1%) and of the central nervous system (seizures 94.2%, mental retardation 51.4%), followed by renal (32.2%), cardiac (25.8%) and ocular (22.5%) manifestations. Among cutaneous manifestations, hypomelanotic macules (94.3%), facial angiofibromas (40%), shagreen spots (20%), fibrous plaques on the forehead (5.7%) and ungula fibromas (5.7%) were observed. Tonic seizures (37.1%) and infantile spasms (21.2%) accounted for majority of seizures. Neurophysiological development was normal in 25.6% of cases, retarded in 51.4% and borderline in 23%. Thirty-four patients had typical pathological findings on magnetic resonance imaging (MRI).In conclusion, the earliest and most frequent complaint is seizure in cases with TS. Careful investigation for hypomelanotic macules and other skin manifestations typical for TS in cases presenting with convulsion makes early diagnosis possible and obviates unnecessary investigations.
Keywords: tuberous sclerosis; seizure; neurocutaneous syndrome